1993
DOI: 10.1007/bf00321190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of below- and aboveground competition from the vines Lonicera japonica and Parthenocissus quinquefolia on the growth of the tree host Liquidambar styraciflua

Abstract: Detrimental effects of vines on tree growth in successional environments have been frequently reported. Little is known, however, about the relative importance of below and aboveground competition from vines on tree growth. The objective of this study was to quantify and compare the growth responses of Liquidambar styraciflua saplings to below and/or aboveground competition with the exotic evergreen vine, Lonicera japonica (Japanese honeysuckle), and the native deciduous vine, Parthenocissus quinquefolia (Virg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
1
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 28 publications
6
101
1
6
Order By: Relevance
“…L. japonica, like other invasive vines, can inhibit growth of host species through light interception and even kill host species through girdling [67]. L. japonica has been shown to inhibit reproduction and growth of non-host trees through root competition around forest edges [34]. In addition, L. japonica can indirectly inhibit growth of native species through site occupation and seedling suppression [30,33,68].…”
Section: Discussionmentioning
confidence: 99%
“…L. japonica, like other invasive vines, can inhibit growth of host species through light interception and even kill host species through girdling [67]. L. japonica has been shown to inhibit reproduction and growth of non-host trees through root competition around forest edges [34]. In addition, L. japonica can indirectly inhibit growth of native species through site occupation and seedling suppression [30,33,68].…”
Section: Discussionmentioning
confidence: 99%
“…Among soil resources altered by trenching are the availability of water and of nitrogen. Several authors have reported a two-fold increase in water [11,12,13], and others have shown an increase in the availability of nitrogen for different forest types ( [44] for deciduous and evergreen forest in North America, [21] for spruce plantations in Europe and [41] for tropical lower montane forest in the Caribbean).…”
Section: Introductionmentioning
confidence: 99%
“…Sin lianas el suelo de un bosque tropical perdería hasta un 40% de hojarasca (Hegarty 1990) y muchos animales sufrirían al escasear la comida y los refugios (Montgomery & Sunquist 1978;Emmons & Gentry 1983;Galetti & Pedroni 1994citado por Morellato & Leitão-Filho 1996. Estructuralmente, las lianas constituyen una red natural de fibras tramadas entre los árboles que proveen estabilidad arquitectural al bosque (Putz 1984), aunque su presencia paradójicamente representa un fuerte perjuicio para la salud del árbol huésped (Putz 1984;Stevens 1987;Clark & Clark 1990;Dillenburg et al 1993).…”
Section: Introductionunclassified